The use of cycling workstations in public places – an observational study. Issue 11 (November 2015) - Torbeyns, T.; Bailey, S.; de Geus, B.; Meeusen, R.
Abstract: Objectives: To determine the use of cycling workstations in public places; how long are they used, who uses them, and why do people use them. Study design: Mixed methods study; observations in combination with questionnaires. Methods: Cycling desks with a charging feature (We-bike) at Brussels National Airport and Brussels South railway station were observed. Data about the number of users, time spent using the workstation, cycling and charging behaviour, were collected by observation. Data about sex, age, body mass index (BMI) and the reason of the use, were obtained via a survey. Results: Approximately three people per hour cycled on the workstation. Mean (SD) cycling time was 15.2 (11.9) minutes and mean (SD) cycling intensity was 2.11 (1.16) on the modified Borg scale. 88% of the users charged a device. About two-thirds of the observed people were male and the majority was between 26 and 45 years old (44%). The average BMI (SD) of the surveyed participants was 24.0 (3.1) kg/m 2, with 26.1% of the participants being overweight. People used the desks because they thought it was fun, relaxing, a good distraction, healthy, good for maintaining shape and/or eco-friendly. However, the majority of the participants (83%) used it because of the charging feature and only one-third of the people would also use the desk if a charging feature was not available. Conclusions: Cycling desks at public places are used by approximately three people per hour. The charging feature is an important motivating factor as only one-third of the people would use the cycling workstation if there would not be a charging feature. As this easy-to-use machine brings about a decrease in sedentary behaviour and an increase in energy expenditure, the availability at places accessible to everyone, could contribute to a less sedentary society and could thus contribute to the prevention of diseases and mental problems related to prolonged sitting.